2012
DOI: 10.1111/and.12028
|View full text |Cite
|
Sign up to set email alerts
|

In vitroeffect of gold and silver nanoparticles on human spermatozoa

Abstract: The cytotoxicity of Au/Ag nanoparticles (NPs) on human spermatozoa was investigated in vitro. Semen from donors were incubated (37 °C, 60'-120') with 30, 60, 125, 250 and 500 μM Au/Ag-NPs. Sperm motility was evaluated following WHO guidelines; sperm viability was assessed with eosin Y test. Au-NPs were characterised and localised with field emission gun-based scanning transmission electron microscope/energy dispersive spectroscopy and transmission electron microscopy. Both tested NPs exerted a significant dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 22 publications
8
55
2
Order By: Relevance
“…In few studies which have been conducted on mammalian sperm, signs of toxic effect of silver nanoparticles are observed. For example in a study by Moretti et al [18] it has been shown that silver nanoparticles exerted a significant dose-dependent effect on motility and viability of human spermatozoa [19]. Also Asare et al [20] indicated toxic effect of silver nanoparticles against human testicular embryonic carcinoma cell line as well as primary testicular cells of mice [20].…”
Section: Discussionmentioning
confidence: 99%
“…In few studies which have been conducted on mammalian sperm, signs of toxic effect of silver nanoparticles are observed. For example in a study by Moretti et al [18] it has been shown that silver nanoparticles exerted a significant dose-dependent effect on motility and viability of human spermatozoa [19]. Also Asare et al [20] indicated toxic effect of silver nanoparticles against human testicular embryonic carcinoma cell line as well as primary testicular cells of mice [20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the intracellular targeting may pose additional challenges requiring the need of cell-penetrating peptides (e.g., polyarginine, polylysine) for effective intracellular delivery of QDs conjugates, while maintaining the homeostasis and osmotic balance of cells. Reproductive studies have shown the ability of porcine gametes to interact with self-illuminated CdSe/ZnS QDs [58,59] with the necessity to determine the suitable sperm-to-QDs ratio, avoiding or limiting QDs toxicity to sperm function, as observed in previous studies using various nanoparticles [58][59][60][61][62][63][64][65]. In vitro matured Table 2.…”
Section: Qds Labelingmentioning
confidence: 99%
“…Application of noble-metal NPs may impact sperm vitality parameters like motility, morphology and membrane integrity, resulting in impairment of male gametes, which become incapable of fertilization. These effects were observed after incubation of spermatozoa with extremely high concentrations of ligand-free AuNPs and AgNPs (Barchanski et al, 2011;Moretti et al, 2013). This cytotoxic consequence was manifested by failure of chromatin to decondense and in the nucleus structure (Zakhidov et al, 2010).…”
Section: Risk Of the Use Of Nanomaterialsmentioning
confidence: 99%